Spatiotemporal evolution and driving factors of the synergistic effects of pollution control and carbon reduction in China - Qinggang Meng; Xiaolan Chen; Hui Wang; Wanfang Shen; Peixin Duan; Xinyue Liu (Ecological Indicators)
Establishing a new environmental governance model driven by the dual wheels of pollution control (PC) system and carbon reduction (CR) system is an efficient approach for addressing multiple ecological challenges. However, given the broad connotations of pollution control and carbon reduction (PCCR), studies that comprehensively quantify their synergistic effects are scarce. This paper develops a coupling coordination indicator system for PCCR grounded in the concepts of “source emission reduction” and “end-of-pipe treatment”. Subsequently, a modified coupling coordination degree (CCD) model is used to calculate the CCD of PCCR in China from 2011 to 2021. The distribution patterns, transition probabilities, and driving mechanisms of the CCD of PCCR are explored using kernel density estimation, Markov chains, and geographically and temporally weighted regression (GTWR). The findings indicate that a preliminary model for coordinated development in PCCR has been established. However, regional disparities in PCCR, a persistent and dynamically evolving feature, manifested a spatial pattern of “higher in the east, lower in the west”. The kernel density distribution curves of the CCD of PCCR in the four major regions showed varying distances of rightward shifts. The absolute differences in the CCD of PCCR in the eastern, western, and northeastern regions narrowed, whereas those in the central region widened. Additionally, a pronounced trend of multipolar differentiation in the CCD of PCCR was evident in the eastern region. Nationally, and particularly in the central region, a pattern of bipolar differentiation gradually formed, while in the western and northeastern regions, the distribution curves transitioned from bimodal or multimodal to unimodal. The development trends of the CCD of PCCR across Chinese provinces were relatively stable, exhibiting a “rich-get-richer” club convergence phenomenon. Overall, the drivers displayed zonal or patch-like spatial differentiation characteristics. Green innovation, digital economy, energy intensity, and human capital drivers showed a clear east–west zonal distribution. This paper provides methodological support for quantitatively evaluating the synergistic effects of PCCR, and its findings offer a reference for regions to develop differentiated PCCR synergy governance strategies.